Abundance and Distributional Patterns of Benthic Peracarid Crustaceans From the Atlantic Sector of the Southern Ocean and Weddell Sea - Di Franco, Davide; Linse, Katrin; Griffiths, Huw J.; Haas, Christian; Saeedi, Hanieh; Brandt, Angelika (Frontiers in Marine Science, 2020)
Climate change is influencing environmental variables in the Southern Ocean and this will have an effect on the marine biodiversity and its composition. Peracarid crustaceans are one of the dominant and most species-rich groups of the Southern Ocean (SO) benthos. To date, knowledge on the influence of environmental variables in shaping abundance and species composition in the SO peracarids is limited, and with regard to ice coverage it is unknown. The aim of our study was to assess the influence of sea ice coverage, chlorophyll-a and phytoplankton concentrations on abundance and distribution of peracarids. In addition, the influence of other physical parameters on peracarid abundance was assessed, including depth, temperature, salinity, sediment type, current velocity, oxygen, iron, nitrate, silicate and phosphate. Peracarids were sampled with an epibenthic sledge (EBS) in different areas of the Atlantic sector of the SO and in the Weddell Sea. Sampling areas were characterised by different regimes of ice coverage (the ice free South Orkney Islands, the seasonally ice-covered Filchner Trough and the Eastern Antarctic Peninsula including the Prince Gustav Channel which was formerly covered by a perennial ice shelf). In total 64766 individuals of peracarids were collected and identified to order level including five orders: Amphipoda, Cumacea, Isopoda, Mysidacea, and Tanaidacea. Amphipoda was the most abundant taxon, representing 32% of the overall abundances, followed by Cumacea (31%), Isopoda (29%), Mysidacea (4%), and Tanaidacea (4%). The Filchner Trough had the highest abundance of peracarids, while the South Orkney Islands showed the lowest abundance compared to other areas. Ice coverage was the main environmental driver shaping the abundance patterns of peracarids and the latter were positively correlated with ice coverage and chlorophyll-a concentration. We propose that the positive correlation between sea ice and peracarid’s abundances is likely due to phytoplankton blooms triggered by seasonal sea ice melting which might increase the food availability for benthos. Variations in ice coverage extent and seasonality due to climate change would strongly influence the abundance and community structure of benthic peracarids.